Dysregulated C1q and CD47 in the aging monkey brain: association with myelin damage, microglia reactivity, and cognitive decline - DeVries, Sarah A.; Dimovasili, Christina; Medalla, Maria; Moore, Tara L.; Rosene, Douglas L. (Frontiers in Immunology, 2024)
Normal aging, though lacking widespread neurodegeneration, is nevertheless characterized by cognitive impairment in learning, memory, and executive function. The aged brain is spared from neuron loss, but white matter is lost and damage to myelin sheaths accumulates. This myelin damage is strongly associated with cognitive impairment. Although the cause of the myelin damage is not known, microglia dysregulation is a likely contributor. Immunologic proteins interact with microglial receptors to modulate microglia-mediated phagocytosis, which mediates myelin damage clearance and turn-over. Two such proteins, “eat me” signal C1q and “don’t eat me” signal CD47, act in opposition with microglia. Both C1q and CD47 have been implicated in Multiple Sclerosis, a demyelinating disease, but whether they play a role in age-related myelin pathology is currently unknown. The present study investigates C1q and CD47 in relation to age-related myelin degeneration using multilabel immunofluorescence, RNAscope, and confocal microscopy in the cingulum bundle of male and female rhesus monkeys across the lifespan. Our findings showed significant age-related elevation in C1q localized to myelin basic protein, and this increase is associated with more severe cognitive impairment. In contrast, CD47 localization to myelin decreased in middle age and oligodendrocyte expression of CD47 RNA decreased with age. Lastly, microglia reactivity increased with age in association with the changes in C1q and CD47. Together, these results suggest disruption in the balance of “eat me” and “don’t eat me” signals during normal aging, biasing microglia toward increased reactivity and phagocytosis of myelin, resulting in cognitive deficits.